2018
DOI: 10.1530/ec-18-0259
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surgery on fat mass, lipid and glucose metabolism in mild primary hyperparathyroidism

Abstract: ContextMild primary hyperparathyroidism has been associated with increased body fat mass and unfavorable cardiovascular risk factors.ObjectiveTo assess the effect of parathyroidectomy on fat mass, glucose and lipid metabolism.Design, patients, interventions, main outcome measures119 patients previously randomized to observation (OBS; n = 58) or parathyroidectomy (PTX; n = 61) within the Scandinavian Investigation of Primary Hyperparathyroidism (SIPH) trial, an open randomized multicenter study, were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
(52 reference statements)
2
14
0
2
Order By: Relevance
“…A recent meta-analysis on the effect on echocardiography measures of surgical treatment in PHPT could not demonstrate signs of reversibility neither in observational nor randomized studies (124). The findings are in accordance with biochemical markers of insulin resistance and CV-risk based on 2 and 5-year data from the randomized Scandinavian study of PHPT (121, 125). Even though a positive treatment effect of surgery on vitamin D levels (25(OH)D) was demonstrated, no effect was seen on body composition and various measures of insulin resistance 5 years following randomization (116, 125).…”
Section: Primary Hyperparathyroidismsupporting
confidence: 87%
“…A recent meta-analysis on the effect on echocardiography measures of surgical treatment in PHPT could not demonstrate signs of reversibility neither in observational nor randomized studies (124). The findings are in accordance with biochemical markers of insulin resistance and CV-risk based on 2 and 5-year data from the randomized Scandinavian study of PHPT (121, 125). Even though a positive treatment effect of surgery on vitamin D levels (25(OH)D) was demonstrated, no effect was seen on body composition and various measures of insulin resistance 5 years following randomization (116, 125).…”
Section: Primary Hyperparathyroidismsupporting
confidence: 87%
“…of follow-up (1.17 ± 0.11 mmol/L) [67]. On the other hand, other researchers have shown that parathyroidectomy did not lead to any significant change in lipid profile [68]. The differences in favour of non-surgically treated patients have been attributed to lipid-lowering therapy.…”
Section: Reviewmentioning
confidence: 92%
“…Long-term treatment effect of surgery on CV-risk markers in the debated mild form of PHPT was recently published based on five-year data from the Scandinavian study (SIPH), (59). Out of the original 191 patients with mild PHPT randomized to either immediate surgery or observation without intervention, 119 concluded the five-year follow-up.…”
Section: Reversibility Of Cv-risk In Phptmentioning
confidence: 99%